Piano Concerto No. 2 - "Aux fins de quelques siècles" - Barlow, Klarenz, 1945- (Mnémothèque Internationale des Sciences et Arts en Musique Électroacoustique, 1961)
Recording of Clarence Barlow's Piano Concerto No. 2 - "Aux fins de quelques siècles". This work started as the second movement of the composers Piano Concerto No. 1 in D and as years past and music changed, the piece changed as well. The composer notes the musical differences throughout the progression of the piece as a reflection of the decade it was written. It was premiered as an orchestral piece in Reykjavik with soloist Deborah Richards and the Iceland Symphony Orchestra.